LITERATURE REVIEW: : ´´THE INFLUENCE OF TREATMENT WITH GnRH ANALOG IN THE FINAL HEIGHT BEFORE AND AFTER EARLY PUBERTY ´´ - Roberta Ribeiro de Marins, Naiara (2021)
Earl puberty begins with activation of the gonadotrophic axis before 8 years of age in girls and at 9 years of age in boys. One of the main concerns is the height because it accelerates the bone maturation process resulting in reduced height. The standard treatment for precocious puberty is the use of deposits of GnRh analogues with the proposal to minimize the effects on growth. As a result, this literature review is based on demonstrating the effects of using GnRh analogues at the final height. Before and after 8 years of age.